2012
DOI: 10.1103/physrevb.85.205410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental determination of the Lorenz number in Cu0.01Bi2Te2.7

Abstract: Nanostructuring has been shown to be an effective approach to reduce the lattice thermal conductivity and improve the thermoelectric figure of merit. Because the experimentally measured thermal conductivity includes contributions from both carriers and phonons, separating out the phonon contribution has been difficult and is mostly based on estimating the electronic contributions using the Wiedemann-Franz law. In this paper, an experimental method to directly measure electronic contributions to the thermal con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…Additionally, a quantitative discussion on carrier density and mobility is more reasonable by using a two-band model. 36,37 Thermal conductivity k xx of polycrystalline NbP is shown in Fig. 4a, k xx increases rapidly with increasing temperature and reaches a peak value of B65 W m À1 K À1 near 85 K then decreases slowly to B39 W m À1 K À1 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a quantitative discussion on carrier density and mobility is more reasonable by using a two-band model. 36,37 Thermal conductivity k xx of polycrystalline NbP is shown in Fig. 4a, k xx increases rapidly with increasing temperature and reaches a peak value of B65 W m À1 K À1 near 85 K then decreases slowly to B39 W m À1 K À1 at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the phonon energy in this temperature range is sufficient to change a 'hot' electron to 'cold,' and vice versa, as shown in Fig. 77 For this reason, when Lukas et al 78 experimentally determined the Lorenz number of Bi 0.88 Sb 0.12 , they measured up to temperatures around 140 K, whereas the onset of the bipolar thermal conductivity effect occurred at temperatures higher than 150 K. Below 140 K, they found that those are matched with eqn (8). An electron can be categorized as hot or cold depending on whether the energy of the electron is higher or lower than the Fermi energy.…”
Section: Comments On the Wiedemann-franz Lawmentioning
confidence: 94%
“…37 In our case, the scattering parameter was determined as 1 according to the dependence of the Hall mobility m H on temperature T revealed in Fig. 5b.…”
Section: Thermal Transport Propertiesmentioning
confidence: 99%